If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4 + 7k) = 265 (4 * 5 + 7k * 5) = 265 (20 + 35k) = 265 Solving 20 + 35k = 265 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 35k = 265 + -20 Combine like terms: 20 + -20 = 0 0 + 35k = 265 + -20 35k = 265 + -20 Combine like terms: 265 + -20 = 245 35k = 245 Divide each side by '35'. k = 7 Simplifying k = 7
| -2s+-26=8 | | 4x^2-12x-52=0 | | 14-0.2(15q+35)=-4q-12 | | 6-1/12-3-11/12= | | 6-4=-x/4 | | 8-v=4 | | 6+3r=18 | | 43d^2-28d=0 | | 6(x+4)=5+2(3-2x) | | -x+8*-23.1=675 | | 61/2-311/12= | | -3+9-22=x | | 2b-20-2=-2 | | 3(x+4)=5+2(3-2x) | | -3+9-22= | | 3n=78.12 | | 3D-4= | | u-8/-1=-1 | | 4(0.25)+x=5 | | I-8/-1=-1 | | a=b/10 | | 8x-8=13-3x+5-2x | | 2x+(x+30)=135 | | 3(2x-1)=7(x+2) | | 2=2c-8+-2 | | 3(2y-1)=7(x+2) | | 13x^5=360 | | 8(-4x+8)=192 | | 11a+12=109 | | 2g+20-10=-8 | | (4x+2)-(-9x^2+x)= | | 8-4(-x-11)-5(x+9)=13x |